Employer impression as amoderator relationship for employer satisfaction with engineering graduates skill at malaysia manufacturing industry - Saleh, H. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
The purpose of this study is to examine the effect of employer impression (EI) as a moderator variable on employer satisfaction for engineering graduates employability at Malaysia manufacturing industry. For this study, Statistical Program for Social Science (SPSS) method version 22 have been use to investigate 195 respondent from Melaka, Negeri Sembilan and Pulau Pinang using questionnaire distribution to the senior management. The statistical method have revealed that EI was significant as the moderator for employer satisfaction to engineering graduates. The result offer important practical implications for applicant’s success in jobs search depend on the EI of skill and engineering graduates’ ability. As far as author knowledge, this study is among the first examining the interactions of EI as the moderatos effect for engineering graduate employability.